History of Lithuania in Cinema and Television. Peculiarities of discourse construction - Rūta Šermukšnytė (Lietuvos Istorijos Studijos)
The aim of the article was to take a look at the peculiarities of construction of historical discourse in documentary cinema and television from the perspective of the contemporary history science. The raised goal was specified by the following tasks: 1. To motivate the beginning and relevance of the selected research in the introductory part; 2. To describe the essence of audio-visual history following the works of Western (mainly German) authors; 3. To discuss the particularity of documentary films and broadcasts dealing with historical topics which have been created during Lithuania's independence, having employed a certain classification.